Effectiveness of Lecture Method in Improving Dental and Oral Health Knowledge in Adolescent Group at Mahasaraswati University Denpasar - Dewi, I Gusti Agung Ayu Chandra Iswari; Idaryati, Ni Putu; Rahina, Yudha; Palgunadi, I Nyoman Panji Triadnya; Lily, Gusti Ayu Yohanna; Pratama, I Wayan Agus Wirya; Pramesti, I Gusti Ayu (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction : Dental and oral health is one of the main indicators of overall health which includes the condition of the oral cavity, frequently encountered diseases, tooth loss and other health problems. One group that is quite vulnerable to dental and oral problems is teenagers, as many as 51.9% of teenagers aged 15-24 years suffer from dental and oral diseases caused by a lack of dental and oral health maintenance behavior. Dental health to increase awareness of teenagers in maintaining dental and oral health. Methods :. This research is a descriptive, cross-sectional observational study in which exposure and outcome are measured at the same time. The research sample was determined by purposive sampling, namely the research sample criteria determined by the researcher and the total sample obtained was 16 samples. The data collection technique used primary data taken using pretest and post-test questionnaires. The data were then analyzed using the Paired Sample T-Test and chi square methods to see differences in knowledge, attitudes and actions before and after counseling. Results and Discussions : A significance value of <0.05 from the paired t-test indicates that there is an influence or significant difference in the respondent's knowledge before and after being given education Knowledge and attitudes will have a big impact on a person's decision to maintain their health. In the chi square analysis test, there was not much difference in the p-value Conclusion : The outreach activities were able to provide an increase in teenagers' knowledge of dental and oral health, marked by the increase in post-test results that were distributed. With increased knowledge in a group of teenagers, it is hoped to reduce the level of dental problems in a group of teenagers